Pengaruh Kualitas Produk Dan Online Customer Review Terhadap Keputusan Pembelian Produk Minuman Es Teh Indonesia Di Yogyakarta The Influence Of Product Quality And Online Customer Reviews On The Decision To Purchase Indonesian Ice Tea Drink Products In Yo - Fadila, Fransiska Nur; Ekawati, Elfi; Sari, Eliza Oktaliana (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2024)
This research aims to determine and analyze the influence of Product Quality and Online Customer Reviews on purchasing decisions for Indonesian Iced Tea beverage products (Case Study of Yogyakarta Indonesian Iced Tea Consumers). This research is a type of quantitative research with data collection materials in the form of questionnaires. The population in this research are consumers who have purchased Indonesian Iced Tea products in Yogyakarta. The sample for this research was taken using probability sampling using a simple random sampling method of 384 samples. Data analysis techniques use instrument tests, classical assumption tests, and multiple linear regression tests. From the research results, it can be concluded that product quality has a significant influence on the decision to purchase Indonesian Iced Tea drink products in Yogyakarta. Online customer reviews have a significant influence on purchasing decisions for Indonesian Iced Tea drink products in Yogyakarta. Product quality, online customer reviews simultaneously influence consumer purchasing decisions for Indonesian Iced Tea drink products in Yogyakarta.